Iddah Bagi Wanita Hamil Yang Ditinggal Mati - Misbahul Amin, M.; Nabila, Mar'atun (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
There are two kinds of divorce in a family, the first occurs when the husband and wife are still alive and the second occurs when one of them dies. The obligation of women when a divorce occurs is to carry out iddah. Iddah is a period that must be awaited by a woman who has been divorced from her husband so that she can remarry to find out that her womb is clean or to carry out Allah's commands. A pregnant woman whose husband dies her iddah ends in childbirth. If a pregnant woman is left behind by her husband, then this is a topic of discussion among scholars. The majority of scholars are of the opinion that the woman underwent a period of iddah until she gave birth to a child